The Impact of the Guide Vane on the BIWT System for the Distributed Wind Generation in the Urban Area - Sim, G.Y.; Ariff, M.A.M.; Goh, H.H.; Ramli, S. N.; Sim, S.Y.; Chien, S.K. (International Journal of Integrated Engineering, 2020)
This paper reports a study on the impact of the guide vane on the Building Integrated Wind Turbine (BIWT) system for the distributed wind generation in the urban area. The guide vane is combined with the rotor to concentrate and accelerate the incoming wind to drive the turbine for power generation. The improved BIWT system has several advantages over the conventional BIWT system; it does not require the structural reinforcement of the building because it generates electricity based on the wind pressure acting on the building’s wall. Furthermore, the guide vane conceals the rotor from the view of pedestrians to maintain the aesthetic value of the building. The analysis focuses on the installation of the BIWT design at a high-rise building. The study evaluates the wind dynamics characteristic on the building’s wall using the computational fluid dynamics (CFD) software. Consequently, the producible power output is estimated based on the wind dynamics characteristic. The effectiveness of the BIWT with the guide vane is evaluated on the actual wind data measured at Kota Kinabalu, Sandakan and Kudat. The result shows that the guide vane increases the producible power output by 129.09%.